New technologies for exploration and exploitation of oil and gas resources : Volume 2 - Commission of the European Communities (London : Graham & Trotman, 1979)
This 2 volumes are outcomes of a symposium organised by the Commission of the European Communities held in Luxemburg from 18-20 April, 1979 on new technologies for exploration and exploitation of oil and gas resources.
"Commission of the European Communities symposium, Luxembourg, April 18-20, 1979"--Cover.
Includes bibliographical references.
lje 22/01/2019
Loans
Keywords: Petroleum; Natural gas; Petroleum in submerged lands; Natural gas in submerged lands